Effects of ellipsoidal and regular hexahedral particles on the performance of the waste heat recovery equipment in a methanol reforming hydrogen production system. (8th April 2023) - Shen, Yingkai; Zheng, Bin; Sun, Peng; Qi, Chenglu; Wang, Mingchao; Dong, Yuanjin; Wang, Youtang; Lv, Jinsheng; Wang, Yunfei
Abstract: Hydrogen production from methanol has attracted attention due to its wide range of raw material sources and mature technology. Using waste heat of industrial high temperature solid particles like blast slag and steel slag etc. To provide vaporization heat and reaction heat for the reaction between methanol and water is an emerging technology for hydrogen production from methanol, which can save additional thermal energy resources. Herein, the performances of equipment that uses the waste heat of ellipsoidal and regular hexahedral particles to provide a heat source for methanol to hydrogen were explored by the DEM-CFD method. Compared with spherical particles of the same equivalent diameter, ellipsoidal and regular hexahedral particles have poor fluidity in the stagnant area, and the empty area is enlarged and irregular in shape. The average velocity peaks of the ellipsoidal and regular hexahedron particles are larger than those of spherical particles, and the overall mean velocity fluctuation of ellipsoidal particles is similar to that of spherical particles while the regular hexahedron particles' is larger. The average temperature drop rate of the ellipsoidal and regular hexahedral particles is slower than that of spherical particles, the uniformity of temperature distribution is worse than that of spherical particles. The ellipsoidal and regular hexahedral particles' average effective heat transfer coefficient is smaller than that of spherical particles, and the heat transfer effect is weaker than that of spherical particles. The effective heat transfer coefficient of ellipsoidal particles is 2.95 W/(m −2 ∙K −1 ) lower than that of spherical particles and the effective heat transfer coefficient of hexahedral particles is 6.09 W/(m −2 ∙K −1 ) lower than that of spherical particles. Therefore, compared with the spherical particles of the same equivalent diameter, ellipsoidal and regular hexahedral particles produce less hydrogen. Highlights: A moving bed heat exchanger model with non-spherical particles was established. The flow properties of ellipsoidal and hexahedral particles were investigated. The effects of different particles on hydrogen production were investigated.